We Aren't So Different After All: Differences and Similarities Between Political Affiliation and Issues of Park Use, Management, and Privatization. (27th December 2018) - Mueller, J. Tom; Mowen, Andrew J.; Graefe, Alan R.
Abstract: Many researchers have argued that political polarization has increased dramatically over the past 25 years. This article explores partisan polarization regarding specific issues of state park use, management, and privatization. An online demographically stratified panel survey of New York and Pennsylvania residents was used to examine differences in attitudes toward these issues by political affiliation. Respondents were placed into three categories: Republican, Independent, and Democrat. While significant differences were found among the groups, they were often small and rarely between Democrats and Republicans. The only issues demonstrating clear partisan differences were certain park privatization issues, support for diversity initiatives, support for additional greenways, and support for shale gas development within state parks. The results from this study indicate little partisan polarization of state park issues.